Chemosensitizing indomethacin-conjugated dextran-based micelles for effective delivery of paclitaxel in resistant breast cancer therapy. - Weiping Ji; Bo Wang; Qiuping Fan; Chao Xu; Youwu He; Youfen Chen (PLoS ONE, 2017)
Multidrug resistance (MDR) against chemotherapeutic agents has become the major obstacle to successful cancer therapy and multidrug resistance-associated proteins (MRPs) mediated drug efflux is the key factor for MDR. Indomethacin (IND), one of the non-steroidal anti-inflammatory agents, has been demonstrated to increase cytotoxic effects of anti-tumor agents as MRP substrates. In this study, dextran-g-indomethacin (DEX-IND) polymeric micelles were designed to delivery paclitaxel (PTX) for the treatment of MDR tumors. The DEX-IND polymer could effectively encapsulate PTX with high loading content and DEX-IND/PTX micelles present a small size distribution. Compared with free PTX, the release of PTX from DEX-IND/PTX micelles could be prolonged to 48 h. Cellular uptake test showed that the internalization of DEX-IND/PTX micelles by drug-sensitive MCF-7/ADR cells was significantly higher than free PTX benefiting from the inhibitory effect of IND on MRPs. In vitro cytotoxicity test further demonstrated that DEX-IND/PTX micelles could enhance the cytotoxicity of PTX against MCF-7/ADR tumor cells. In vivo pharmacokinetic results showed that DEX-IND/PTX micelles had longer systemic circulation time and slower plasma elimination rate in comparison to PTX. The anti-tumor efficacy test showed that DEX-IND/PTX micelles exhibited greater tumor growth-inhibition effects on MDR tumor-bearing mice, with good correlation between in vitro and in vivo. Overall, the cumulative evidence indicates that DEX-IND/PTX micelles hold significant promise for the treatment of MDR tumors.